PENEGAKAN HUKUM TERHADAP KENDARAAN BERMOTOR ANGKUTAN BARANG MENGENAI TATA CARA PEMUATAN DAYA ANGKUT DAN DIMENSI KENDARAAN BERDASARKAN UNDANG- UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU - Abdillah, Muhammad Fadil; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The presence of large-dimensional vehicles and large capacity is a factor causing road damage and high fasalitas for road users in Pekanbaru City. The obligation to comply with the provisions of goods shall be regulated in Article 169 paragraph (1) of Law Number 22 Year 2009 regarding LLAJ which reads